Means of recording ownership right under the agreement - Сурженко, О. А. (Theory and practice of jurisprudence, 2016)
The article is a study of means of ownership right acquisition. Special attention is given to such a way of ownership right acquisition, which is contained only in the law, without any other volitional actions on the part of the transmittee. The notion of ownership right transfer by means of its delivery and the meaning thereof as a lawful fact with the respective requirements to formation thereof is given.